Chemokines as effector and target molecules in vascular biology. (12th May 2015) - Sozzani, Silvano; Del Prete, Annalisa; Bonecchi, Raffaella; Locati, Massimo
Abstract: Chemokines are key mediators of inflammation. In pathological tissues, the main roles of chemokines are to regulate leucocyte accumulation through the activation of oriented cell migration and the activation of limited programs of gene transcription. Through these activities, chemokines exert many crucial functions, including the regulation of angiogenesis. The 'chemokine system' is tightly regulated at several levels, such as the post-transcriptional processing of ligands, the regulation of the expression and function of the receptors and through the expression of molecules known as 'atypical chemokine receptors', proteins that function as chemokine scavenging and presenting molecules. Several experimental evidence obtained in vitro, in animal models and in human studies, has defined a crucial role of chemokines in cardiovascular diseases. An intense area of research is currently exploring the possibility to develop new effective therapeutic strategies through the identification of chemokine receptor antagonists.